A completely human-derived biomaterial mimicking limbal niche: Platelet-rich fibrin gel. (August 2018) - Dereli Can, Gamze; Akdere, Özge Ekin; Can, Mehmet Erol; Aydın, Bahri; Cagil, Nurullah; Gümüşderelioğlu, Menemşe
Abstract: Platelet-rich fibrin (PRF) is a natural biomaterial and has excellent biochemical and physical properties with a history of proven biocompatibility in the field of tissue engineering and regenerative medicine. Recent reports of fibrin-based matrices have offered new opportunities to apply PRF as a supplement for in vitro cell culture. Here, custom-modified human-derived PRF (HPRF) was produced via different centrifugation protocols, then, characterized by morphologically and chemically and utilized as a substrate and as a conditioned medium for limbal explant culture for the first time. It was found that the HPRF released significantly higher levels of growth factors which are essential for epithelial cell growth. The enhanced physicochemical properties of the HPRF were also proven in the limbal explant cultures in terms of cell growth, migration, viability, and stemness in comparison with the conventional limbal explant culture on human-derived amniotic membrane. Consequently, HPRF hydrogels are appealing natural biomaterials for the purpose of mimicking limbal niche and the discovery elucidates this new, xeno-chemical-free, completely human-derived biomaterial can be utilized as a supplement to promote epithelial cell behaviour in vitro . Highlights: Investigation of xeno-chemical-free cell culture systems is a growing area. Mimicking in vivo conditions with biosafe methods is essential for clinical purpose. Choukroun's PRF was first used as substratum and conditioned medium for limbal culture. It promotes epithelial cell growth, migration, viability, and stemness. The applicability of this new concept has to be proven through clinical studies.